2023
DOI: 10.1177/23800844231165016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Dental Care Utilization and Oral Health Conditions in the United States

Abstract: Purpose: We aim to understand the impact of the COVID-19 on health care utilization and oral health conditions of patients at federally qualified health centers (FQHCs), where patients are disproportionately low income, publicly insured, or uninsured. Methods: Using deidentified electronic health records of patients at FQHCs in the United States from January 2019 through December 2020 ( n = 431,509), variations in health care utilization since the COVID-19 outbreak were observed by procedure types and patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This may be due to the difference in the profile of patients arriving to dental clinics during the pandemic. During lockdown periods dental clinics provided mainly urgent treatment for acute painful conditions and most subjects avoided in-office consultations for non-painful conditions [54]. The fact that the prevalence of painful and non-painful TMD during the pandemic was almost similar in both genders further supports this notion.…”
Section: Discussionmentioning
confidence: 84%
“…This may be due to the difference in the profile of patients arriving to dental clinics during the pandemic. During lockdown periods dental clinics provided mainly urgent treatment for acute painful conditions and most subjects avoided in-office consultations for non-painful conditions [54]. The fact that the prevalence of painful and non-painful TMD during the pandemic was almost similar in both genders further supports this notion.…”
Section: Discussionmentioning
confidence: 84%
“…The COVID-19 pandemic had an impact on the accessibility of dental services by people which had a devastating effect on the oral health of the people. 14 This study was conducted to explore the experiences and general attitudes of people during the COVID-19 pandemic. With the closure of clinics, the people looked for alternate solutions to their problems.…”
Section: Discussionmentioning
confidence: 99%
“…People in the United States reported the impact of COVID-19 on the oral health of the public, they faced difficulty in scheduling appointments and worsened their hygiene and eating habits. 14 Several studies reported an increase in sugar consumption. Most studies concluded that there was an increase in the provision and utilization of emergency oral health services like tooth extractions, and orthodontic emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals were reported to be more likely to experience surgery visits and less likely to experience preventive and restorative visits. 20 Although tele dentistry became more common during the coronavirus period, providing dental consultation, instructions, and treatment planning, it coincided with a decrease in the overall number of dental visits. Patients received delayed treatment during this time, which resulted in more invasive procedures.…”
Section: Covid-19mentioning
confidence: 99%
“…These obstacles during the COVID-19 period all contributed to the dental status of US individuals. 20…”
Section: Covid-19mentioning
confidence: 99%